From the Editors: Student samples in international business research - Bello, Daniel; Leung, Kwok; Radebaugh, Lee; Tung, Rosalie L; van Witteloostuijn, Arjen (Journal of International Business Studies, 2009)
The JIBS Statement of Editorial Policy states that “Empirical submissions utilizing undergraduate student samples are usually discouraged.” Wording is important here – “usually” does not imply “always.” This statement suggests that while student samples are appropriate, in principle, undergraduate ones are not, except in unusual situations. The purpose of this From the Editors column is to discuss the pros and cons of student samples in international business (IB) research. Are student samples appropriate for developing and testing IB theories? When are student samples appropriate, and when are they not appropriate? Is there a difference between undergraduate and graduate samples? What are the “best practices”? This editorial is intended to provide IB researchers with guidelines as to when student samples, and which types of student samples, are appropriate in IB research.